2002
DOI: 10.1016/s0041-624x(02)00259-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurement of gas flow using electrostatic transducers

Abstract: Ultrasonic gas flowmeters typically use narrowband piezoelectric transducer arrangements for interrogating the flow of gas in a pipe. In this work, the suitability of broadband electrostatic transducers operating at frequencies of up to 1 MHz for ultrasonic measurement of gas flow has been investigated. The transit time method of ultrasonic gas flow measurement was adopted and experiments were carried out using a laboratory test rig capable of producing a range of gas flowrates up to 17.5 m/s. The test rig als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
(25 reference statements)
0
11
0
1
Order By: Relevance
“…The field of air-coupled ultrasonics has received an increased interest over the years, as it has expanded into new areas of application, including wireless communication [1], contactless material characterisation [2], gas flow metering [3], [4] and robotics [5]. Each application has its own set of requirements, which has pushed the development of transducer technology.…”
Section: Introductionmentioning
confidence: 99%
“…The field of air-coupled ultrasonics has received an increased interest over the years, as it has expanded into new areas of application, including wireless communication [1], contactless material characterisation [2], gas flow metering [3], [4] and robotics [5]. Each application has its own set of requirements, which has pushed the development of transducer technology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for the application discussed here, the measurement configuration as shown in Fig. 1 basically has two advantages in comparison to a configuration with the transducers showing protrusion into the main flow [12], namely 1) transducer membranes are located in regions where the temperature is lower, and 2) temperature gradients along the transducer membrane surfaces are lower due to the fact that the membranes are not located in the region (close to the center of the pipe) where the temperature distribution normally shows a steep gradient.…”
Section: Discussionmentioning
confidence: 99%
“…A high-temperature-resistant broadband CUT is used both for transmitting and receiving the ultrasonic pulses [11]. Nowadays, CUTs are accepted as state-of-the-art transducers for gas flow measurement applications, e.g., [12]. By modifying the construction of the commonly used CUTs, which, for instance, utilize a metallized polymer membrane as the moving electrode, and by selecting appropriate transducer materials, we have achieved a wideband CUT for operation at elevated gas temperatures of up to several hundred degrees Celsius.…”
mentioning
confidence: 99%
“…(O'Sullivan, Wright, 2002) demonstrated that capacitive ultrasonic transducers (CUTs) are in general a promising transducer technology for UFMs. The advantages are the excellent bandwidth characteristics (up to 100% fractional bandwidth in air at 101.325 kPa), and the reduced acoustic impedance mismatch to gases at lower pressures compared to piezoelectric transducers.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages are the excellent bandwidth characteristics (up to 100% fractional bandwidth in air at 101.325 kPa), and the reduced acoustic impedance mismatch to gases at lower pressures compared to piezoelectric transducers. The CUTs used in (O'Sullivan, Wright, 2002) had a metallized polymer membrane as moving electrode, which makes them unsuitable for a wider temperature range. The advent of a high-temperature version of these CUTs, as reported in (Schr€ o oder et al, 2004), eliminated this temperature limitation by transferring the insulation layer from the movable electrode to the backplate of the CUT.…”
Section: Introductionmentioning
confidence: 99%